Alih Aksara dan Alih Bahasa Teks Kitab Ilmu Kaji Diri dan Ilmu Firasat - Sella Melati; Hasanuddin WS Hasanuddin WS (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2020)
The objectives of this study include: (a) presenting a description of the script of Kitab Ilmu Kaji Diri dan Ilmu Firasat, (b) presenting the transliteration result of the text of the Kitab Ilmu Kaji Diri and Ilmu Firasat, (c) displaying the translation of Kitab Ilmu Kaji Diri dan Ilmu Firasat from old Malay into Indonesian. This research is categorized in the type of philological research. The object of this research is the text of Kitab Ilmu Kaji Diri dan Ilmu Firasat. This research method is a philological research method adapted to the research stages and descriptive methods. The data collection stage used the literature study or observation method and at the script description stage the descriptive method was used. Furthermore, for the transliteration stage the transliteration method or the transliteration method is used, then the language transfer process uses the language transfer method. The results of this study are (1) a complete description of the manuscript, (2) transcription of the text of Kitab Ilmu Kaji Diri dan Ilmu Firasat from Arabic-Malay into Latin without changing the type of language that can be read and understood by today’s society. (3) The text of Kitab Ilmu Kaji Diri dan Ilmu Firasat has been translated from old Malay to Bahasa Indonesia. Some of the vocabularies of the Malay language vocabulary contained in the script of Kitab Ilmu Kaji Diri dan Ilmu Firasat are still preserved to maintain the originality of the old vocabulary.